Is the good life the easy life? - SCOLLON, Christie N. (Institutional Knowledge at Singapore Management University, 2004)
Three studies examined folk concepts of the good life. Participants rated the desirability and moral goodness of a life as a function of the happiness, meaning, and effort experienced. Happiness and meaning were solid predictors of the good life, replicating King and Napa (1998). Study 1 (N = 381) included wealth as an additional factor. Results showed little desire for exorbitant (over moderate) wealth, but also a desire to avoid poverty. When effort was operationalized as number of hours worked, respondents desired the easy life, particularly at moderate levels of income. When effort was operationalized as effortful engagement (Study 2), 186 undergraduates and 178 community adults rated the hardworking life as morally superior to the easy life. Community adults preferred meaningful lives of ease, while college students preferred meaningful lives that involved effort. Study 3 (N = 359) found the meaningful, effortful life was rated as most morally good, and the happy effortful life was rated as most desirable, happy, and meaningful. The role of hard work in naïve notions of The Good Life is discussed.